2020
DOI: 10.1186/s13098-020-0516-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sodium–glucose cotransporter 2 inhibitors on renal function in participants with type 2 diabetes and chronic kidney disease with normoalbuminuria

Abstract: Background: We compared the effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors on renal function in participants with type 2 diabetes and chronic kidney disease (CKD) classified by degree of albuminuria. Methods:A retrospective review of the clinical records of Japanese participants with type 2 diabetes (age > 20 years; SGLT2 inhibitor treatment > 2 years; estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 ) was conducted. Based on the urinary albumin-to-creatinine ratio (UACR) or urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the present study, we showed that additional treatment with SGLT2is prevents the decline in eGFR in the SGLT2 group compared with that in the control group. Although we had previously shown that more favorable effects of SGLT2is on renal function in patients with type 2 diabetes and CKD with normoalbuminuria compared with patients with macroalbuminuria [9], this study did not include a control group. Therefore, this study was able to confirm the renoprotective effects on SGLT2is for patients with type 2 diabetes and CKD with normoalbuminuria compared with non-SGLT2is user.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we showed that additional treatment with SGLT2is prevents the decline in eGFR in the SGLT2 group compared with that in the control group. Although we had previously shown that more favorable effects of SGLT2is on renal function in patients with type 2 diabetes and CKD with normoalbuminuria compared with patients with macroalbuminuria [9], this study did not include a control group. Therefore, this study was able to confirm the renoprotective effects on SGLT2is for patients with type 2 diabetes and CKD with normoalbuminuria compared with non-SGLT2is user.…”
Section: Discussionmentioning
confidence: 99%
“…Four large prospective clinical trials have shown that SGLT2is decrease the composition renal endpoints such as decline in estimated glomerular filtration rate (eGFR), doubling of the serum creatinine level, new end-stage kidney disease, death from renal or cardiovascular causes, or progression to macroalbuminuria [3][4][5][6]. In addition, it has been reported that, in patients with type 2 diabetes and chronic 6 kidney disease (CKD), SGLT2is prevent the decline in eGFR [7][8][9][10]. However, studies on the effects of SGLT2is on renal function in patients with type 2 diabetes and CKD with normoalbuminuria remain limited [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four large prospective clinical trials have shown that SGLT2is decrease the composition renal endpoints such as decline in estimated glomerular filtration rate (eGFR), doubling of the serum creatinine level, new end-stage kidney disease, death from renal or cardiovascular causes, or progression to macroalbuminuria [4] , [5] , [6] , [7] . In addition, it has been reported that, in patients with type 2 diabetes and chronic kidney disease, SGLT2is prevent the decline in eGFR [8] , [9] , [10] , [11] . However, studies on the effects of SGLT2is on renal function in patients with type 2 diabetes and CKD with normoalbuminuria remain limited [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that, in patients with type 2 diabetes and chronic kidney disease, SGLT2is prevent the decline in eGFR [8] , [9] , [10] , [11] . However, studies on the effects of SGLT2is on renal function in patients with type 2 diabetes and CKD with normoalbuminuria remain limited [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%